Clean and Healthy Living Behavior to Prevent Acute Respiratory Infection among Farmer's Families - Enggal Hadi Kurniyawan; Ahmad Hykal Adlan Zein; Selvia Amelinda Novianti; Ivada Dea Nintiarso; Kholid Rosyidi Muhammad Nur; Dicky Endrian Kurniawan; Alfid Tri Afandi; Ida Zuhroidah (Health and Technology Journal (HTechJ), 2024)
Acute Respiratory Infection (ARI) cases in Indonesia and abroad are still a significant health problem. In Indonesia, ARI ranks first as a cause of death in infants and toddlers, with a mortality rate of around 20-30%. ARI can cause severe breathing difficulties, such as pneumonia, and ARI is also one of the leading causes of death in children under the age of five in developing countries. This study aims to analyze how to improve clean and healthy living behavior to prevent ARI in farmer families. The research method used was a literature review conducted through Google Scholar, PubMed, and Science Direct in the 2019-2024 range. The keywords used in the search for articles were "ARI, Respiratory Disorders," "Unhealthy Living Behavior, Reduced Working Period, Well Ventilated House," and "Farmer, Family". Researchers found ten studies that met the inclusion criteria in the review. Prevention of respiratory tract infections (URI) in farming families involves practicing healthy behaviors, such as washing hands with soap, maintaining environmental hygiene, and avoiding exposure to cigarette smoke. The articles highlight the importance of understanding knowledge and adherence to clean and healthy living behaviors (PHBS) in reducing the risk of ARI. However, therapeutic communication is also essential, through providing clear information and emotional support to change unhealthy behaviors. The article still has obstacles, such as the underutilization of sanitation clinics, which calls for a more intensive and focused therapeutic communication approach to overcome these obstacles. Factors that increase the risk of Acute Respiratory Infection (ARI) include cooking with biogas inside the house, high housing density leading to a lack of sanitation around the house, poor ventilation, heavy workload for farmers, which increases exposure to dust, smoke and toxic gases, intense smoking, lack of access or awareness of the benefits of local sanitation clinics, and lack of awareness of the importance of maintaining environmental sanitation. Nurses are expected to conduct community counseling to improve understanding of clean and healthy behavior in ARI prevention practices among farmers.